Analysis of professional secrecy in Ibero-America: Ethical and legal perspectives. (October 2022) - Estrada-Cuzcano, Alonso; Alfaro-Mendives, Karen Lizeth
Eight Ibero-American political constitutions that include professional secrecy (confidentiality) as a constitutional guarantee are analysed, and their influence as a fundamental right in the professional practice of librarians is examined. The impact of professional secrecy is established in professional codes of ethics, and it is shown that they do not clearly express this principle; its application in trade unions has limited effectiveness. The various difficulties involved in preserving professional secrecy in library practice, which work centres try to violate, are shown.